School manuals for teaching geography at the Sovereign State of Santander: 1868-1879 (2015)
This article presents at least three objectives. The irst of them:to evidence the legislative aspects of the Organic Decree of Public Primary Instruction –ODPPI– of 1870 in relation to the topic of school manuals, the school knowledge of geography and the way in which it was evaluated. Secondly, this paper presents an identiication and description of the content and dissemination of some of the geography school manuals that existed in the Sovereign State of Santander during the last three decades of the 19th century. Finally, we present the ways in which some teachers from Santander resisted the initiative to consolidate the printed text as the main reference for the dissemination of school knowledge. Based on the previous information, this article comprises four sections which deal with the aforementioned topics. Therefore, it was conirmed that ODPPI regulated the subject of school manuals, to the point of identifying some of the directly responsible agents of its achievement and monitoring. Likewise, geography, as school knowledge, was regulated within the curricula. Besides, evidence shows that geography school manuals did not include as much printed material as subjects like arithmetic or reading. Equally, geography was found to be taught under the following categories: Universal and Colombian and Regional. Finally, even though the State taught the importance of the print text, other voices emerged in defense of oral teaching methods, which made it possible to identify that the consolidation of printing as a diffusion system for culture was not an easy lineal task.